Polyphenol nanoformulations for cancer therapy: experimental evidence and clinical perspective - Davatgaran-Taghipour Y (Dove Medical Press, 2017)
Yasamin Davatgaran-Taghipour,1,2 Salar Masoomzadeh,3 Mohammad Hosein Farzaei,4,5 Roodabeh Bahramsoltani,6 Zahra Karimi-Soureh,7 Roja Rahimi,6,8 Mohammad Abdollahi9,10 1Department of Medical Nanotechnology, School of Advanced Technologies in Medicine, Tehran University of Medical Sciences, Tehran, Iran; 2PhytoPharmacology Interest Group (PPIG), Universal Scientific Education and Research Network (USERN), Tehran, Iran; 3Zanjan Pharmaceutical Nanotechnology Research Center, School of Pharmacy, Zanjan University of Medical Sciences, Zanjan, Iran; 4Pharmaceutical Sciences Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran; 5Medical Biology Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran; 6Department of Traditional Pharmacy, School of Traditional Medicine, Tehran University of Medical Sciences, Tehran, Iran; 7School of Pharmacy, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 8Evidence-Based Medicine Group, Pharmaceutical Sciences Research Center, Tehran University of Medical Sciences, Tehran, Iran; 9Toxicology and Diseases Group, Pharmaceutical Sciences Research Center, Tehran University of Medical Sciences, Tehran, Iran; 10Department of Toxicology and Pharmacology, Faculty of Pharmacy and Pharmaceutical Sciences Research Center, Tehran University of Medical Sciences, Tehran, Iran Abstract: Cancer is defined as the abnormal cell growth that can cause life-threatening malignancies with high financial costs for patients as well as the health care system. Natural polyphenols have long been used for the prevention and treatment of several disorders due to their antioxidant, anti-inflammatory, cytotoxic, antineoplastic, and immunomodulatory effects discussed in the literature; thus, these phytochemicals are potentially able to act as chemopreventive and chemotherapeutic agents in different types of cancer. One of the problems regarding the use of polyphenolic compounds is their low bioavailability. Different types of formulations have been designed for the improvement of bioavailability of these compounds, nanonization being one of the most notable approaches among them. This study aimed to review current data on the nanoformulations of natural polyphenols as chemopreventive and chemotherapeutic agents and to discuss their molecular anticancer mechanisms of action. Nanoformulations of natural polyphenols as bioactive agents, including resveratrol, curcumin, quercetin, epigallocatechin-3-gallate, chrysin, baicalein, luteolin, honokiol, silibinin, and coumarin derivatives, in a dose-dependent manner, result in better efficacy for the prevention and treatment of cancer. The impact of nanoformulation methods for these natural agents on tumor cells has gained wider attention due to improvement in targeted therapy and bioavailability, as well as enhancement of stability. Today, several nanoformulations are designed for delivery of polyphenolic compounds, including nanosuspensions, solid lipid nanoparticles, liposomes, gold nanoparticles, and polymeric nanoparticles, which have resulted in better antineoplastic activity, higher intracellular concentration of polyphenols, slow and sustained release of the drugs, and improvement of proapoptotic activity against tumor cells. To conclude, natural polyphenols demonstrate remarkable anticancer potential in pharmacotherapy; however, the obstacles in terms of their bioavailability in and toxicity to normal cells, as well as targeted drug delivery to malignant cells, can be overcome using nanoformulation-based technologies, which optimize the bioefficacy of these natural drugs. Keywords: natural products, flavonoid, anthocyanin, tumor, malignancy